Dampak Disclosure Sustainibility Report Terhadap Profitabilitas Perusahaan Industri Dasar dan Kimia - Vastuvica, Vinsensia; Ayu, Stephana Dyah (Jurnal Ilmiah Wahana Akuntansi, 2023)
This research is obtaining empirical evidence about the impact of the Disclosure Sustainability Report on profitability. The Disclosure Sustainability Report is proxied by the Economic Disclosure Index (EcDI), Environmental Disclosure Index (EnDI), and Social Disclosure Index (SoDI). Profitability is proxied by Return on Assets (ROA) and Gross Profit Margin (GPM). The population of this research is companies in the basic industry and chemicals sector listed on the Indonesia Stock Exchange (2020-2022). The amount of sample is 12 companies which was determined by the purposive sampling method. Data was processed using SPSS (Statistical Program for Social Science), by multiple linear regression analysis and hypothesis testing. Regression analyzed there’s influence of the Disclosure Sustainability Report on Profitability, but partially each variable EcDI, EnDI, and SoDI doesn’t significantly impact profitability.